AB0289 Clinical Value of the Antinuclear Antibodies in the Rheumatoid Arthritis: A Study of 170 Patients. (9th June 2015) - Jguirim, M.; Mani, L.; Mhenni, A.; Zrour, S.; Younes, M.; Béjia, I.; Touzi, M.; Bergaoui, N.
Abstract : Background: The diagnosis of rheumatoid arthritis (RA) notably that of early arthritis, rests on a cluster of clinical and biological arguments. Among biological test, three families of autoantibodies have been selected: anti-citrullinated peptide Antibodies (ACPA), rheumatoid factor (RF) and antinuclear Antibodies (ANA) Objectives: The objective of this study is to determine the clinical value of antinuclear antibodies in rheumatoid arthritis Methods: A total of 170 patients were included with the diagnosis of rheumatoid arthritis meeting ACR 1987 criteria, in a retrospective study, between 1997 and 2014. Clinical, biological, radiological characteristics and comorbidities were assessed for each patient. Results: The average age was 48.8 years [16- 86]. The predominance was for woman with a sex ratio 8.4. The average disease duration was 4 years [1-36]. An initial assessment by the DAS 28 showed that 70% of patients had high activity and 30% had moderate disease activity. Joint deformities were reported in 36% of cases. Extra-articular manifestations were reported in 46.5% of patients. Radiological destruction was observed in 76% of cases. The most prevalent comorbidities in this population were anemia (37.6%), osteoporosis (21.2%), diabetis (16.5%) and hypertension (11.8%) and 4 cases of renal failure. All patients received corticosteroids and 89% received methotrexate. 70 patients were followed over a period of 60.8 months. Of these patients, 67% had low disease activity, 20% had a moderate disease activity and 13% were non-responders. We used a biotherapy in only four patients. Seronegative rheumatoid arthritis was found in 20% of cases. RF was positive in 72% of cases, ACPA were positives in 42% of cases. ANA was positive in 14.7% of cases, among these patients we found positive anti SSA +/- SSB in six cases, positive anti RNP in four cases and positive anti DNA in tow cases. The diagnosis of Sjögren's syndrome associated with RA was retained in six cases. Conclusions: The search for ANA is used for differential diagnosis with other auto immune diseases such as Sjögren's syndrome, scleroderma and lupus erythematosus. But ANA can exist in 20%>45% of RA patients usually at a low rate. References: Dijkmans D, van Schaardenburg D, van der Horst-Bruinsma IE, Reesink HW, Vandenbroucke JP, Boers M.The predictive value of autoantibodies in disseminating lupus erythematosus and rheumatoid arthritis. Ned Tijdschr Geneeskd. 2005;149:688-93. Disclosure of Interest: None declared